Supporting data for analysis of the Helicobacter pylori exoproteome - Snider, Christina A. (Data Brief, 2015)
The goal of this research was to analyze the composition of the Helicobacter pylori exoproteome at multiple phases of bacterial growth (Snider et al., 2015) [1]. H. pylori was grown in a serum-free medium and at serial time points, aliquots were centrifuged and fractionated to yield culture supernatant, a soluble cellular fraction, and a membrane fraction. Samples were analyzed by single dimensional LC-MS/MS analyses and multidimensional protein identification technology (MudPIT). Here we present data showing the numbers of assigned spectra and proportional abundance of individual proteins in each of the samples analyzed, along with a calculation of the level of enrichment of individual proteins in the supernatant compared to the soluble cellular fraction.